Analisis Hubungan Kebiasaan Konsumsi Dengan Kuantitas Sampah Domestik: Studi Pada Mahasiswa Pendidikan Biologi Untirta Angkatan 2020 - Utari, Enggar; Putri Pramudita, Wida; Pratiwi, Zulia (ECOTAS, 2023)
Domestic waste is waste that comes from human daily activities in the household which does not include feces and specific waste. Domestic waste is divided into two based on its nature, namely organic waste and anorganic waste. The purpose of this study was to determine the comparison of the amount of domestic waste produced by 5th semester students of Untirta Biology Education during a period of one week. as for the analytical method used in this study is a quantitative descriptive approach. The results of the study found that anorganic waste had a higher amount, namely with a percentage of 65% compared to organic waste with a percentage of 35%. This difference can be caused by the advantages possessed by anorganic waste to help human daily activities and the existence of housing for students such as living with parents or living in boarding houses or dormitories